A Trip Through the Emergency Department: Cost-Conscious Care - Emily McIsaac; Jennifer Walthall; Adam Sharp (Association of American Medical Colleges, 2014)
Abstract Introduction Evidence-based medicine is now the gold standard of care in the United States, and physicians will be challenged to incorporate new standards of care, including cost conscious care. Though medical research now has some focus on economics in medicine, further emergency medicine-specific scholarship is important to improve care in this unique setting. Recent literature has outlined the areas where emergency physicians should change practice patterns to improve cost efficiency and possibly improve patient outcomes, as physicians will have more fiscal responsibility in their clinical decision making to cut down costs on a larger scale This resource provides a discussion of health care economics that can be easily incorporated into daily practice to improve the efficiency of the overall health care system. Methods This module contains an hour-long didactic session. It includes a brief introduction with a worksheet to spark the learners' curiosity and encourage discussion points. The presentation is 30 minutes in length. After the presentation, the learners are asked to revisit the worksheet and discussion points, and participate in a 20-minute discussion of cost-effective care challenges and implementation. Faculty leadership should be available to provide guidance and expertise. Results The module was presented as an hour-long didactic session for medical students, residents, and faculty at an emergency medicine academic center. Feedback from the session was overall positive. There was some desire by the learners to include discussions on tort reform, patient satisfaction, and the current government health care model. Discussion Physicians in general have a poor understanding of the economic ramifications of their clinical decision making on their patients, and both medical students and residents receive minimal training in this area anecdotally. This resource helps provide a portion of this understanding. It should be noted that due to the breadth of this topic, it was limited to focusing on how health care providers can be better advocates for their patients in reference to health care spending. The session benefited from having the hospital medical director and a faculty researcher in cost-effective care present. These faculty mentors provided unique points of view but were not essential to the discussion of this topic.